2017
DOI: 10.1038/nn.4482
|View full text |Cite|
|
Sign up to set email alerts
|

Circuit specificity in the inhibitory architecture of the VTA regulates cocaine-induced behavior

Abstract: Afferent inputs to the ventral tegmental area (VTA) control reward-related behaviors through regulation of dopamine neuron activity. The nucleus accumbens (NAc) provides one of the most prominent projections to the VTA; however, recent studies have provided conflicting evidence regarding the function of these inhibitory inputs. Using optogenetics, cell-specific ablation, whole cell patch-clamp and immuno-electron microscopy, we found that NAc inputs synapsed directly onto dopamine neurons, preferentially activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
145
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(157 citation statements)
references
References 56 publications
12
145
0
Order By: Relevance
“…Previous studies including more recent optogenetic approaches have suggested that GABA B receptor-targeting neurons arise from the nucleus accumbens and regulate drug-induced behaviors (Sugita et al, 1992; Cameron and Williams, 1993; McCall et al, 2017; Edwards et al, 2017). However, our earlier work found no LTP GABA at GABA B synapses on dopamine neurons (Nugent et al, 2009), suggesting that the effects of persistently activated κORs are unlikely to involve the nucleus accumbens-VTA GABAergic afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies including more recent optogenetic approaches have suggested that GABA B receptor-targeting neurons arise from the nucleus accumbens and regulate drug-induced behaviors (Sugita et al, 1992; Cameron and Williams, 1993; McCall et al, 2017; Edwards et al, 2017). However, our earlier work found no LTP GABA at GABA B synapses on dopamine neurons (Nugent et al, 2009), suggesting that the effects of persistently activated κORs are unlikely to involve the nucleus accumbens-VTA GABAergic afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evidence supports neurochemical and physiological heterogeneity of VTA GABAergic neurons (Margolis et al, 2012; Morales and Margolis, 2017). In particular, GABA A receptors may be expressed by VTA DA neurons as well as local GABAergic interneurons (Edwards et al, 2017). Therefore, depending on the population of intra-VTA GABA A receptors activated, one can have an inhibitory or permissive effect on firing of VTA DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both cocaine and morphine increase locomotor activity but through different mechanisms. That is, activation of GABA B receptors expressed in dopaminergic neurons in the VTA is involved in the regulation of cocaine‐induced locomotion but not affects morphine‐induced locomotion . Therefore, although both morphine and cocaine increase locomotor activity, the downstream signaling that underlies this phenomenon may be quite different.…”
Section: Strategy To Investigate Dopamine‐independent Opioid Rewardmentioning
confidence: 99%